Helical flow in tortuous aortas and its relationship to turbulence: A whole-aorta 4D flow MRI study - Dyverfeldt, Petter; Trenti, Chiara; Ziegler, Magnus; Bjarnegård, Niclas; Lindenberger, Marcus (Frontiers in Cardiovascular Medicine, 2023)
Background Increased vascular tortuosity is a hallmark of ageing of the vascular system, including the aorta. However, the impact of tortuosity on aortic blood flow is unknown. We hypothesized that increased tortuosity would be associated with increased blood flow helicity and with decreased degree of blood flow turbulence as measured by the turbulent kinetic energy (TKE). Methods 4D Flow MR images covering the entire aorta from the aortic valve to the iliac bifurcation were acquired in 23 normal volunteers aged 18-30 years (“Young”) and 23 normal volunteers aged 66-76 years (“Old”) without aortic disease. The aorta was segmented and divided into four regions: the ascending, descending, suprarenal abdominal and infrarenal abdominal aorta. Tortuosity, helicity, TKE, flow velocity, and Reynolds number were computed for the whole aorta and for each section. Results Tortuosity and helicity were higher whereas TKE, velocity, and Reynolds number were lower in Old than in Young, for all aortic regions (p < 0.05) except for helicity in the descending aorta. Tortuosity correlated positively with helicity and negatively with TKE for all aortic regions (Spearman rho = ±0.45 – ±0.72, p <= 0.002) except for TKE in the ascending aorta. Further, helicity correlated with TKE in the descending, suprarenal abdominal and infrarenal abdominal aorta (Spearman rho = -0.56 – -0.77). Conclusion Tortuosity increases with age and blood flow in tortuous aortas is more helical. Increasing helicity, in turn, is associated with decreasing TKE.